Targeting IL-1β in the Treatment of Atherosclerosis - Mai, Wuqian; Liao, Yuhua (Frontiers in Immunology, 2020)
The role of inflammation in atherosclerosis has been recognized several decades ago and existing treatments provide benefits in part through non-specific anti-inflammatory actions. Compared with other cytokines, interleukin-1β（IL-1β） is associated with acute and chronic inflammation. Anti-inflammatory therapy with canakinumab targeting the IL-1β innate immunity pathway could significantly reduce the rate of recurrent cardiovascular events than placebo, the results of CANTOS suggested an important role of IL-1β in atherosclerosis. However, there are numerous mechanisms that are to be clarified. We herein discussed the important immunomodulatory effect IL-1β exerts on atherosclerosis and the potential mechanisms underlying it. We also reviewed bench-to-bedside clinical translation of IL-1β neutralizing strategies associated with the use of IL-1β blockade in patients with atherosclerosis.